Contextualização, escola quilombola, relações étnico-raciais : aproximações e distanciamentos no livro didático de ciências - Bispo, Agnes Gardênia Passos (2018)
The present study it has as objective to understand the identified approximations and distances between the proposed contextualization of the of Natural Sciences’ Textbook from the 6th grade used in a school located in Sergipe's quilombola territory, and the one exposed in the National Curriculum Guidelines for School Education Quilombola. The guidelines set forth in the National Curriculum Guidelines for School Education Quilombola (DCNEEQ) and in the National Curriculum Guidelines for Ethnic Racial Relations Education (DNERER) point out need to work on themes that respect the specificities of the students. The methodological approach defended in this study is based on qualitative research. The analysis was based on Freire's theoretical assumptions, the CTS approach and the DCNEEQ and DCNERER orientations. The Teacher’s Guide, images of black people present in the volume and the proposal of contextualization were analyzed, considering their limits and possibilities, approaching this problematization of the quilombola school context. Five categories of analysis were elaborated from the theoretical supports and the orientations of the official documents, such as: relevance of themes, scope of themes, emergence of themes, disciplines and / or knowledge involved and theme and content relation. In summary, we have contacted the images of the adult black people identified and analyzed in this paper that, although presenting a significant representation of Brazilian ethnic-racial diversity - with the presence of black, indigenous and white people - these images illustrate less prestigious work Social. On the other hand, the images of black children adequately demonstrated the Brazilian diversity, since, in addition to the significant amount of images of children of different ethnicities, they were equally represented in various everyday situations. As possibilities we also point out the story of a black biologist, who may be provocative of the reflection on the contribution of black scientists and, particularly, black women to scientific development. On the contextualization we conclude from the analysis of the sections Facts and Ideas, It was News and Debates Forum, that the relevance of the topics addressed has as a concern scientific and technological aspects relating to social issues. The scope of the themes is mostly universal. There is no relationship proposal with other disciplines. The discussion with social issues restricts the scope of the discipline. The relation theme and content is practically all based on universal knowledge. On this we realize that, in the Debates Forum section, there is a suggestion for students to do research on the topic and discuss the subject. However, none of the proposed debates promote the inclusion of students' knowledge and identities. Thus the idea of Science as a single and absolute truth permeates the whole book, just as the idea that it is produced by white men. In a similar way, because of the little problematization of ethnic-racial relations, the idea that can continue to spread is that in our country whites, blacks and indigenous people live in harmony. It is also worth noting that even though it is a book of use throughout the national territory, it is necessary to promote the insertion of the diverse cultures that form the Brazilian people and, more specifically, in the teaching of reflection on how scientific knowledge contributes and contributes to the maintenance of social inequalities. Finally, as a proposal for contextualization, we propose that daily life be the starting point and the point of arrival and the need to build more possibilities for the reflection on the various forms of knowledge production by humanity. We still point out that no reference is made to the ethno-racial question. Similarly, there is no reference to the history and identities of the quilombolas, but images were found of black people placed in situations of slavery.